Large intestinal fermentation capacity of fattening pigs on organic farms as measured in vitro using contrasting substrates. (25th March 2013) - Sappok, Maria; Pellikaan, Wilbert F; Verstegen, Martin WA; Bosch, Guido; Sundrum, Albert; Hendriks, Wouter H
Abstract Background In accordance with the EU regulations, organic farms require pigs to be fed diets high in fibre, which may impact on the pigs' large intestinal fermentation capacity. The ability of pigs to ferment non‐starch polysaccharides (NSP) depends on characteristics of the dietary NSP source and microbes present in the large intestine of pigs. Little information exists on the fibre fermentation capacity of organically raised pigs. The aim of this study was to determine the variation in fibre fermentation capacity of fattening pigs within and between organic farms using an in vitro batch culture method and three contrasting substrates: oligofructose, soy pectin and cellulose. Results Pigs from different organic farms showed varying fermentation capacities as assessed by gas production, kinetics and fermentation end‐products formed (P < 0.01). Coefficients of variation between inocula within farms varied by up to 40% for gas production and kinetics, in particular for incubation with cellulose. No relationship between on‐farm feeding practice and the pigs' fermentation capacity could be established. Conclusion The fermentation capacity of pigs reared under organic conditions varies considerable between farms. Finishing pigs reared under organic farming conditions are fast fermenters of oligofructose and soy pectin. More than four donor animals should be used per inoculum to accurately assess in vitro fermentation capacity. Fermentation results could not be related to dietary management under on‐farm conditions. © 2013 Society of Chemical Industry